Diversity of crabs to inform crab-based ecotourism in Bagek Kembar, Lombok, Indonesia - GITO HADIPRAYITNO; I WAYAN SUANA; DIDIK SANTOSO; LALU JAPA; ENI SUYANTRI; GDE CAHYADI WIRAJAGAT; MUHAMMAD SYAZALI; MOHAMMAD LIWA ILHAMDI; RIZKY REGINA KAWIRIAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hadiprayitno G, Suana IW, Santoso D, Japa L, Suyantri E, Wirajagat GC, Syazali M, Ilhamdi ML, Kawirian RR. 2026. Diversity of crabs to inform crab-based ecotourism in Bagek Kembar, Lombok, Indonesia. Biodiversitas 27 (1): d270104. https://doi.org/10.13057/biodiv/d270104. Crabs in mangrove ecosystem in Bagek Kembar, Lombok, Indonesia have potential to be developed as an ecotourism. This research aims to analyze the diversity and abundance of crabs, and to assess the suitability for crab tourism in the Essential Ecosystem Area in Bagek Kembar. Data collection was conducted over three months from June to August 2024 using folding trap and quadrant plot methods. Tourism suitability index was calculated by incorporating several variables, including diversity and evenness indices, number of species, density, and economic value. Sampling conducted using complementary quadrant plots and traditional folding traps (Bubu) documented 16 crab species from 5 families, with all recorded taxa categorized as Not Evaluated by the IUCN. Community structure was characterized by strong dominance of fiddler crabs (Ocypodidae), particularly Austruca annulipes (31.69% relative density), and overall diversity and distribution were relatively stable (Shannon-Wiener H’ = 2.195, evenness E = 0.792). Quadrant plots captured broader assemblage richness (13 species) including visually attractive, behaviorally distinctive fiddler crabs, whereas Bubu traps mainly captured three economically important edible species (Scylla olivacea, Scylla serrata, and Thalamita crenata), confirming a clear separation between observation-oriented and culinary-oriented tourism assets. The modified Tourism Suitability Index integrating diversity, density, species number, economic value, and evenness yielded a score of 2.6, classifying the area as highly suitable for developing crab-focused tourism.